2023
DOI: 10.3949/ccjm.90a.22019
|View full text |Cite
|
Sign up to set email alerts
|

Central sensitization, chronic pain, and other symptoms: Better understanding, better management

Abstract: Central sensitization, a pathophysiologic process in which the central nervous system undergoes changes that alter its processing of pain and other sensory stimuli, may be the mechanism underlying various conditions in which patients have unexplained pain and fatigue. Patients frequently misunderstand the cause of their symptoms and pursue unnecessary evaluations and treatments. Clinicians have a pivotal role in decreasing this misunderstanding by providing patient education, which can affect perception, manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The “train” of joint nociceptor inputs results in an excessive CNS activation with functional and structural CNS changes. Central sensitization may lead to a combination of three phenomena: hyperalgesia, allodynia, and global sensory hyperresponsiveness [ 81 ] in response to any sensory input coming from the body’s periphery or external environment. Finally, central sensitization can explain spontaneous joint pain without sensory input from the periphery [ 81 ].…”
Section: The Gut–joint Axis: How Dysbiosis Leads To Osteoarthritismentioning
confidence: 99%
“…The “train” of joint nociceptor inputs results in an excessive CNS activation with functional and structural CNS changes. Central sensitization may lead to a combination of three phenomena: hyperalgesia, allodynia, and global sensory hyperresponsiveness [ 81 ] in response to any sensory input coming from the body’s periphery or external environment. Finally, central sensitization can explain spontaneous joint pain without sensory input from the periphery [ 81 ].…”
Section: The Gut–joint Axis: How Dysbiosis Leads To Osteoarthritismentioning
confidence: 99%
“…Both groups have also demonstrated an increased risk for other psychiatric disorders, such as anxiety and depression [ 40 , 41 ]. More recently, it has been suggested that central sensitization—a recognized risk factor in the development and maintenance of chronic pain [ 9 , 11 , 12 , 13 ]—may also play a role in eating disorders [ 42 ].…”
Section: Restrictive Eds In Adolescents With Chronic Functional Abdom...mentioning
confidence: 99%
“…For example, multiple surgeries and/or infections in the same abdominal region could impact the sensitivity of nerve receptors in the gut [ 9 ]. Similarly, central sensitization—when the central nervous system undergoes changes that alter its processing of pain and other sensory stimuli, resulting in a lower pain threshold [ 9 , 10 ] is recognized as a contributor to the development and maintenance of chronic pain [ 11 , 12 , 13 ]. Abdominal pain may lead to food avoidance and dietary restriction, which places individuals at higher risk for developing an eating disorder pathology [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic centralized pain syndromes are extremely important, common, and vexing for both patients and clinicians. In this issue of the Journal, Volcheck et al 1 present a framework that I believe is useful for understanding chronic centralized pain and for developing an actionable treatment plan for patients.…”
mentioning
confidence: 99%
“…While it is always important to keep an open mind and avoid the clinical sin of premature closure, making the diagnosis with confi dence is important. Reassurance and behavioral treatment approaches can be provided, 1,3 and previous patient experiences and symptoms can be explained and even described by the clinician without hearing them from the patient. For example, on "less-bad" days, patients try to accomplish many tasks that they could not do the preceding few days and then end up almost disabled by pain or fatigue for the next several days, by the development of intolerance to touch, strong odors, or noises, by dyspareunia (in women), and by the sensation of pain from frequent culture-negative urinary tract infections (interstitial cystitis).…”
mentioning
confidence: 99%